PENGARUH DESTINATION IMAGE DAN PERCEIVED VALUE TERHADAP KEPUASAN SERTA DAMPAKNYA TERHADAP REVISIT INTENTION (STUDI PADA FESTIVAL BUDAYA CAP GO MEH DI KOTA SINGKAWANG) - admin, NOFIYANTI B11112116 (Jurnal Manajemen Update, 2016)
This research aims to examine and analyze the influence of Destination Image and Perceived Value on satisfaction and its impact on Revisit Intention (Studies on the cultural festival Cap Go Meh in Singkawang). This reseacrh is quantitative. The population in this study are tourists who had watched Culture Cap Go Meh Festival in Singkawang at least 3 years. The sampel of 100 respondents, sampling technique that is used in this research is purposive sampling and then the data was processed by path analysis. Results of the study show that the first model image destination variables, perceived value significant positive effect on satisfaction. Predictive capability of the two variabels on statisfaction is 68,1% while the remaining 31,9%Â  was influenced by other factors not included in the research model. The results of analysis for the second model show that statisfaction have a significant effect on revisit intention. Predictive capability of theÂ  variabel on revisit intention is 38,7% while the remaining 61,3% was influenced by other factors not included in the research model. Keywords: destination image, perceived value, statisfaction and revisit intention Â